KAJIAN KONSEP “CUSTOMIZATION” VITVAL IKEA - Rinkapati Swatriani (Narada : Jurnal Desain dan Seni, 2022)
One of the advantages of the products offered by IKEA is that it carries the concept of "customization". Vitval products apply this concept, namely a bunk bed frame which has empty space at the bottom so that it can be used to create another "space" by placing several pieces of furniture that can be adjusted to the needs of users, the children. The method used is qualitative with descriptive analysis. The results of this study are, as a student, the customization that can be done is Vitval with a study table. In addition, looking at the Vitval size and user anthropometry, some pieces of furniture that can be customized include sofas, cabinets, drawers, shelves, or portable mattresses. Vitval is a solution for parents who want to take advantage of the limited space in their child's room by getting two spaces in one room.